P081: Distribution of take home naloxone in Edmonton zone emergency departments between January 2016 and December 2017. (May 2019) - Lam, N.; Olmstead, A.; Ha, D.; Gauri, A.
Abstract : Introduction : Morbidity and mortality from opioid overdoses continue to be a significant issue worldwide. In Alberta, there was a 40% increase in accidental opioid-related deaths from 2016 to 2017. In response to this crisis, Alberta Health Services has dramatically expanded access to Naloxone with a province-wide program for the distribution of take-home naloxone (THN) kits. Edmonton Zone ED's began dispensing these kits in 2016. The objectives of this study are to assess the trends in THN kit distribution from these sites in 2016 and 2017.Methods : The Edmonton Zone is a health region that comprises eleven tertiary, urban community and rural community ED's. THN kits in Edmonton Zone ED's were distributed through Pyxis, an automated medication dispensing and tracking system. Pyxis data for THN kits in 2016 and 2017 was extracted for each Edmonton Zone ED and the raw numbers and trends were examined. The National Ambulatory Care Reporting System database was also analyzed to determine the number of opioid related visits to Edmonton Zone ED's over that same time period.Results : A total of 686 THN kits in the Edmonton Zone were distributed over 2016 and 2017. The two tertiary centers distributed 502 kits, while the urban and rural community emergency departments collectively distributed 184 kits. Comparing 2016 (n = 245) to 2017 (n = 441), there was an 80% overall increase in the number of kits distributed, with tertiary center ED's dispensing 92% more kits, urban community ED's 51% more and rural ED's 63% more. Over the same time period, the number of opioid related visits increased in tertiary center ED's by 78%, in urban community sites by 26%, and in rural ED's by 67%. Almost all ED's increased their THN kit distribution from year to year, though there was one urban community site that dispensed fewer kits in the second year of the program.Conclusion : Edmonton Zone ED's dispensed 686 THN kits over two calendar years. Almost every ED distributed more kits in 2017 than 2016, which likely reflects successful uptake of this harm reduction intervention by frontline ED staff. However, there is still evidence of some imbalance in THN kit allocation as the percent increase in kits distributed varied widely based on the type of ED. This data can be used to pinpoint areas in the Edmonton Zone where barriers to THN access may still exist and guide continued quality improvement interventions to increase distribution and education.